Enhanced activation of molecular oxygen and degradation of tetracycline over Cu-S4 atomic clusters - Hui Li; Shoutian Sun; Ji, Haodong; Liu, Wen; Zhurui Shen (Applied Catalysis B: Environmental, 2020)
It is quite important and challenging for efficient activating the molecular oxygen (O2) to reactive oxygen species (ROS), especially in environmental remediation. Herein, the CuS4 atomic clusters are constructed on the surface of ZnInS4 nanosheet (CuS4-ZIS), which shows much better ability for activating O2 to ROS than pristine ZnInS4 nanosheet (ZIS) and the CuS3.6 atomic clusters counterpart (CuS3.6-ZIS). Results display that CuS4-ZIS can energetic favorably adsorb the O2 and more electrons could transfer from the CuS4-ZIS to O2 than ZIS and CuS3.6-ZIS. Besides, a better charge separation and transfer is observed on CuS4-ZIS. Thus, higher concentration of superoxide radicals (·O2−, partially transformed into ·OH) can be generated over Cu-S4 atomic clusters under light illumination. Therefore, CuS4-ZIS exhibits higher degradation efficiency of tetracycline (TC) than pristine ZIS and CuS3.6-ZIS. Moreover, the degradation pathway of TC is proposed based on the results of HPLC-MS and the theoretical calculations.
Keywords: Atomic cluster; Degradation and mineralization; O activation; Reactive oxygen species; Tetracycline